(untitled) (Texas Journal of Philology, Culture and History, 2023)
This article discusses specific peculiarities of teaching pronunciation in technical institutions, which has always been one of the most essential matters of methodology of foreign languages. The main aim of the given research is to analyze and suggest the effective methods and ways of teaching pronunciation in technical institutions. Participants of the study were groups of learners of Turin Polytechnic University in Tashkent at intermediate level.